Factorization of pretopological spaces and strong product graphs - Lao, Angelyn R. (Animo Repository, 2004)
The first part of the study discusses the basic concepts of the strong product of graphs including its Factorization Theorem through examples and illustrations. The second part of the paper focuses on definitions, axioms and concepts leading to the study of spaces specifically pretopological space. The third part of this research is an exposition of the state of the art theorem, Factorization of Pretopological Space. Lastly, this paper shows that any finite digraph T(X,E) representing a reflexive relation can always be associated with a finite pretopological space (X,N). Furthermore, a pretopological space (X,N) is factorizable if and only if the strong product of the associated graph is factorizable.